Development of fragility curves of self-supporting trussed towers considering severe wind loading - Robles, Edgar Allan D.; Aquino, Diocel Harold M.; Hernandez, Jaime Y. Jr.; Longalong, Romeo Eliezer U. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The Philippines is a typical pathway of typhoons that bring about heavy winds per year. Self-supporting trussed towers, like any other structures, may experience damage from the exposure on these severe winds. It is therefore beneficial that a tool be made for assessing damage on these structures. Due to insufficiency of data, selfsupporting trussed tower models with randomized geometry were generated considering the data from the acquired structural plans. The models were tested on wind loads on different directions considering wind speeds ranging from 200 kph to 300 kph and a wind speed increment of 10 kph. The damage states are recorded and processed considering the defined damage state descriptions to finally develop the fragility curves. Self-supporting trussed towers were found to be vulnerable to "domino" effect. Also, only the "no damage," "slight damage," and "destruction" states were found to exist on these structures.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Radio and television towers -- Wind-pressure.; Towers -- Aerodynamics